DESCRIPTION OF SCIENCE PROCESS SKILLS OF CLASS VIII STUDENTS OF SMPN IN MAKASSAR CITY - St Aida Sufinasa; Hasanuddin Hasanuddin; Sitti - Saenab; Rifda Nur Hikmahwati Arif; Salma - Samputri; Nur Rajemi Hasan (JURNAL EDUSCIENCE, 2023)
This study aims to describe how big the science process skills of students in class VIII SMPN Makassar city. This research is descriptive correlative with a population of all students of class VIII SMPN Makassar which amounted to 4178 students while the sample amounted to 364 students. The instrument used is a test of science process skills on the material of the human respiratory system in the form of multiple choice. The data collection technique is giving tests to students via google form on even semester VIII class material. The results obtained are the scientific process skills of students in class VIII SMPN Makassar in the human respiratory system material are in the low category.Keywords: science process skillAbstrakPenelitian ini bertujuan untuk mendeskripsikan seberapa besar keterampilan proses sains peserta didik kelas VIII SMPN sekota Makassar. Penelitian ini adalah deskriptif korelatif dengan populasi seluruh peserta didik kelas VIII SMPN sekota Makassar yang berjumlah 4178 peserta didik sedangkan sampel berjumlah 364 peserta didik. Instrumen yang digunakan berupa tes keterampilan proses sains pada materi sistem pernapasan manusia dalam bentuk pilihan ganda. Teknik pengumpulan data yaitu pemberian tes kepada peserta didik melalui google form pada materi kelas VIII semester genap. Hasil penelitian yang diperoleh adalah keterampilan proses sains peserta didik kelas VIII SMPN sekota Makassar pada materi sistem pernapasan manusia berada dalam katagori rendah.Kata Kunci: keterampilan proses sains